Being 'at-home' on outpatient parenteral antimicrobial therapy (OPAT): a qualitative study of parents' experiences of paediatric OPAT. Issue 3 (26th September 2019) - Carter, Bernie; Fisher-Smith, Debra; Porter, David; Lane, Steven; Peak, Matthew; Taylor-Robinson, David; Bracken, Louise; Carrol, Enitan
Abstract : Objective: To better understand the factors that facilitate and hinder a positive experience of paediatric outpatient parenteral antimicrobial therapy (OPAT). Design: Qualitative study using semistructured interviews. Setting: A dedicated paediatric consultant-led hospital-based, outreach OPAT service in England. Participants: Participants were primarily parents of children who had received OPAT; one child participated. Methods: Children and parents of children who received OPAT and who had participated in the survey phase of the larger study were invited to be interviewed. Results: 12 parents (10 mothers and 2 fathers) of 10 children participated; one child (aged 15 years). Data analysis resulted in one meta-theme, 'At-homeness' with OPAT, this reflected the overall sense of home being a place in which the children and their parents could be where they wanted to be. Four key themes were identified that reflect the ways in which parents and children experienced being at-home on OPAT: 'Comfort, security, freedom, and control'; 'Faith, trust and confidence'; 'Explanations and communication' and 'Concerns, restrictions and inconveniences'. Conclusions: Despite feeling anxious at times, parents reported that they and their children generally had a positive experience of OPAT; being at-home brought many benefits compared with in-patient care. Recommendations arising from the study include a 'whole-system' approach to discharge home that includes support related to return to school/nursery, reduction in disruptions to home-based routines, more clarity on choice and preparation for managing potential anxiety, better consideration of dose timing and enhanced preparation and information.